Getting wet: Tales of lesbian seductions - Allain, Carol; Elwin, Rosamund (Women's Press, 1992)
This is sex fiction that gets under the covers and rolls them back, sex fiction that inscribes lesbian erotics poignantly, playfully and powerfully.
Keywords: 1900-1999; amériques; approches et analyses; canada; corps; lesbianisme; périodes historiques; ressource en ligne; régions géographiques; sexualité; thématiques; érotisme

When Jack Blinks: Si(gh)ting gay desire in Ann Bannon's Beebo Brinker - Barale, Michèle Aina (Feminist studies, college park, 1992)
The overtly lesbian story, "Beebo Brinker," by Ann Bannon offers the heterosexual male reader an opportunity to engage in nonheterosexual imaginings. Bannon's story is examined for its subcultural appropriation and subversion as a crossover novel in reverse.
https://www-proquest-com.proxy.bibliotheques.uqam.ca/docview/233183798/fulltextPDF/6501A30CCBE14AACPQ/1?accountid=14719
Keywords: approches et analyses; arts; discipline; hétérosexisme; identités LGBTQIA2+; lesbianisme; ressource en ligne; systèmes d'oppressions; études littéraires